2017
DOI: 10.1103/physrevd.95.025016
|View full text |Cite
|
Sign up to set email alerts
|

Chirped-frequency excitation of gravitationally bound ultracold neutrons

Abstract: Ultracold neutrons confined in the Earth's gravitational field display quantized energy levels that have been observed for over a decade. In recent resonance spectroscopy experiments [T. Jenke et al., Nat. Phys. 7, 468 (2011)], the transition between two such gravitational quantum states was driven by the mechanical oscillation of the plates that confine the neutrons. Here we show that by applying a sinusoidal modulation with slowly varying frequency (chirp), the neutrons can be brought to higher excited stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In particular, in the case  ′′ ( 0 ; , ) > 0, there are two modes corresponding to the simple roots. In the opposite case,  ′′ ( 0 ; , ) < 0, there are two additional modes corresponding to 0 and associated with the particular solutions having asymptotics (6). One of these additional modes with 1 = − is stable on the asymptotically long time interval.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, in the case  ′′ ( 0 ; , ) > 0, there are two modes corresponding to the simple roots. In the opposite case,  ′′ ( 0 ; , ) < 0, there are two additional modes corresponding to 0 and associated with the particular solutions having asymptotics (6). One of these additional modes with 1 = − is stable on the asymptotically long time interval.…”
Section: Resultsmentioning
confidence: 99%
“…• If  ′ ( ; , ) = 0 and  ′′ ( ; , ) < 0, then system (1) has two different solutions * ( ), * ( ) with asymptotic expansion in the form (6).…”
Section: The Roots Of Multiplicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the influence of small oscillatory perturbations on dynamical systems is well-studied problem [16][17][18][19][20]. In particular, chirped-frequency perturbations with a small parameter are effectively used to control the dynamics of nonlinear systems [21][22][23][24][25]. However, in this paper the presence of a small parameter is not assumed.…”
Section: Introductionmentioning
confidence: 99%
“…LC is the quantum counterpart of the classical AR and it is a series of successive two-level Landau-Zener (LZ) transitions, where only two adjacent energy levels of the driven oscillator are coupled at any given time. Compared with AR, the discrete nature of LC is visible only when spectra of the systems is discrete enough, therefore, it is studied only in quantum systems including anharmonic oscillators [13][14][15], Rydberg atom [16] and bouncing neutrons [17]. Interestingly, it is demonstrated that classical systems, for example, Langmuir waves in bounded plasma, also can exhibit LC much like a quamtum system [18,19].…”
Section: Introductionmentioning
confidence: 99%